Maturity Matrices for Institutional Benchmarking of Dam Safety in Indonesia - World Bank (World Bank, Washington, DC, 2018)
The development of Maturity Matrices for Institutional Benchmarking of Dam Safety in Indonesia provides a method for assessing the effectiveness of the operation, maintenance, surveillance and emergency preparedness programs adopted by dam authorities. Matrices were developed for dam owners and operators to assess the effectiveness of dam safety programs against in-country standards and guidelines, or, good industry practice as considered most appropriate. The matrices were developed through an iterative and consultative process that included a detailed review of the legal hierarchy, specific dam safety regulations and technical guidelines, the roles and responsibilities of the different institutions involved, followed by expert review and verification. The primary benefit of using dam safety-related Maturity Matrices is to improve the understanding of dam safety programs across a range of different metrics. This allows owners and operators to monitor performance over time and inform the prioritization of resources for dam operation, maintenance and safety improvement. The matrices also allow regulatory bodies to assess performance across different owners and operators, and contrast the effectiveness across dam management units to identify systemic issues and target interventions and remedies accordingly.